Magnetic field frustration of the metal-insulator transition in V2 O3 - Trastoy, J. (2020)
Despite decades of efforts, the origin of metal-insulator transitions (MITs) in strongly correlated materials remains one of the main long-standing problems in condensed-matter physics. An archetypal example is V2O3, which undergoes simultaneous electronic, structural, and magnetic phase transitions. This remarkable feature highlights the many degrees of freedom at play in this material. In this work, acting solely on the magnetic degree of freedom, we reveal an anomalous feature in the electronic transport of V2O3: On cooling, the magnetoresistance changes from positive to negative values well above the MIT temperature, and shows divergent behavior at the transition. The effects are attributed to the magnetic field quenching antiferromagnetic fluctuations above the Néel temperature TN, and preventing long-range antiferromagnetic ordering below TN. In both cases, suppressing the antiferromagnetic ordering prevents the opening of the incipient electronic gap. This interpretation is supported by Hubbard model calculations which fully reproduce the experimental behavior. Our study sheds light on this classic problem providing a clear and physical interpretation of the nature of the metal-insulator transition.